Hubungan kecerdasan naturalis dan motivasi belajar dengan kemampuan berpikir kritis peserta didik pada materi pencemaran lingkungan - Nabilah Rahma Putri; Mieke Miarsyah; Diana Vivanti (UNIVERSITAS PGRI MADIUN, 2018)
The skills to think critically on environmental pollution material is the skills of the learners to understand a condition that involves the process of reasoning about environmental pollution. Student’s critical thinking skills is an interaction between various factors, namely naturalist intelligence and motivation learning. Student who possess critical thinking skills are as good as those naturalist intelligence and those who are motivated to learn. This study aimed to determine the correlation between naturalist intelligence and motivation learning with student’s critical thinking skills in Jakarta on environmental pollution. This research was conducted at 68 Jakarta Senior High School on semester II of 2017/2018 school year. The method that was used is descriptive quantitative through correlational study. The sample used amount if 115 students of class X MIA. The result of prerequisite test finds that the data are normally distributed and homogeneous. The statistical hypothesis was done by linier regression test, liniearity test, and correlation coefficient test at α = 0,05. Based on these results, it is concluded there is a correlation between naturalist intelligence and motivation learning with student’s critical thinking skills on environmental pollution.